2021
DOI: 10.1016/j.jmig.2020.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Vaginal Natural Orifice Transluminal Endoscopic Hysterectomy for Benign Indications

Abstract: The Hominis surgical system is a novel robot-assisted system, designed specifically for robotic vaginal natural orifice transluminal endoscopic surgery (RvNOTES). We presented our experience of the first 30 RvNOTES hysterectomies assessing the feasibility and safety of this technology. Design: A two-center prospective study. Setting: Academic tertiary referral centers. The ethics committees approved the study in both centers. Patients: Thirty women with benign indication for hysterectomy. Intervention: RvNOTES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…A recent case series of 114 patients described the feasibility performing R‐vNOTES hysterectomy, while comparing 35 cases of R‐vNOTES hysterectomy and 79 traditional vNOTES hysterectomy 16 . Surgical outcomes of both groups of patients were similar, but the study was limited by its small sample size 17,25 . This study appears to be the current largest case series of patients undergoing R‐vNOTES hysterectomy to date, allowing for further analysis of safety of this novel technology and surgical approach.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent case series of 114 patients described the feasibility performing R‐vNOTES hysterectomy, while comparing 35 cases of R‐vNOTES hysterectomy and 79 traditional vNOTES hysterectomy 16 . Surgical outcomes of both groups of patients were similar, but the study was limited by its small sample size 17,25 . This study appears to be the current largest case series of patients undergoing R‐vNOTES hysterectomy to date, allowing for further analysis of safety of this novel technology and surgical approach.…”
Section: Discussionmentioning
confidence: 97%
“…16 Surgical outcomes of both groups of patients were similar, but the study was limited by its small sample size. 17,25 This study appears to be the current largest case series of patients undergoing R-vNOTES hysterectomy to date, allowing for further analysis of safety of this novel technology and surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, all of the surgeries in this study were performed by a single minimally invasive surgeon with great familiarity with single-incision laparoscopy and T-vNOTES before adopting R-vNOTES and may not be generalizable to all surgeons. However, we are still hopeful that this study provides promising evidence for the integration of the robot in vNOTES hysterectomy, especially as robotic platforms developed specifically for use in vNOTES (Hominis surgical system; Memic Innovative Surgery, Portland, ME) have recently been shown to be safe and effective [28].…”
Section: Discussionmentioning
confidence: 96%
“…This platform was specifically designed to facilitate single-incision robotic vaginal natural orifice transluminal endoscopic surgery (RvNOTES), and two prospective clinical studies have reported the performance of eight bilateral salpingo-oophorectomies [87] and 30 hysterectomies [88] to treat benign diseases, with good intra-, peri-, and postoperative outcomes. A rapid learning curve was observed and no device-related adverse events were reported, proving the feasibility and user-friendliness of RvNOTES with this system.…”
Section: Hominis® Surgical Systemmentioning
confidence: 99%